Flight intensity of two species of stingless bees Heterotrigona itama and Geniotrigona thoracica and its relationships with temperature, light intensity and relative humidity - Wan Nur Asiah Wan Mohd Adnan; Ahmad Said Sajap; Nur Azura Adam; Mohd Norowi Hamid (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Information on flight intensity of stingless bees is important in pollinator management programs. However, the flight intensity of local stingless bees especially for Heterotrigona itama and Geniotrigona thoracica is poorly known. Investigations into the pattern of activity of various species of meliponinae, in different parts of the world, reveal a lot of variations. Hence, this study was designated to determine the effect of daytime and climatic factors on the flight of stingless bees. This study was conducted at Orchad 10, Universiti Putra Malaysia, Serdang, Selangor and the flight intensity of bees was determined by counting the numbers of bees leaving and returning to their nest for ten minutes observations. Counting was done in six colonies which had similar strength. It was done five times per day at 8.00 am, 10.00 am, 12.00 pm, 2.00 pm and 4.00 pm for six days. The peak number of bees that exited and returned was recorded around 8.00 am to 10.00 am for both species. The number of Geniotrigona thoracica exited from the entrance had a positive correlated to air temperature, relative humidity and light intensity. Meanwhile for Heterotrigona itama, their flight activities were affected by temperature and light intensity. Hence it is advisable to save stingless bees by not applying insecticide to crops at times of day when their flight intensity is highest.